Environmental management of artisanal activities in gold mining. Case: town of Relave - Iglesias León, Silvia (2002)
The environmental effects produced by the artisanal mining activity in the town of Relave, cause environmental problems and problems in the health of the inhabitants, which can be remedied with the proposal and execution of an environmental management in accordance with the reality of the area. The research project carried out by teachers and students from the Universidad Nacional Mayor de San Marcos, during 2001, demonstrates that the existing working conditions lack technical supervision and it is necessary to establish environmental management, as well as guidelines so that artisanal activities in gold mining are the most optimal. This task must be carried out with the participation of institutions such as the Congress of the Republic, the National Environment Council, the Ministry of Energy and Mines, the Ministry of Health, the Provincial Municipality, Universities and the Ministry of the Interior, among others.